2002
DOI: 10.1186/1471-2458-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of positive health in disability pensioners: a population-based questionnaire study using Positive Odds Ratio

Abstract: Background: Determinants of ill-health have been studied far more than determinants of good and improving health. Health promotion measures are important even among individuals with chronic diseases. The aim of this study was to find predictors of positive subjective health among disability pensioners (DPs) with musculoskeletal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Ejerlertsson has shown that being an immigrant is related to poor health (29). These findings agree with the results found in this study.…”
Section: Discussionsupporting
confidence: 95%
“…Ejerlertsson has shown that being an immigrant is related to poor health (29). These findings agree with the results found in this study.…”
Section: Discussionsupporting
confidence: 95%
“…The odds ratios were calculated in an ordinary way, but in line with the salutogenetic approach the positive and negative outcome in the dependent variable, as well as in the explanatory variables, were changed and expressed as positive odds ratios (POR) [18]. …”
Section: Methodsmentioning
confidence: 99%
“…The chi-square test was used to test the association of sociodemographic and health care factors with the practice of BSE and Pap smear screening. Odds ratios (OR) were calculated and interpreted as positive odds ratios (POR), following the example of Ejlertsson et al [12], who had defined the POR as an indicator of positive health or practices rather than the conventional odds ratio that is used as a measure of risk. For ease of interpretation, the OR was consistently calculated for the group with a higher proportion of positive health behaviour compared to the group with a lower proportion of positive health behaviour.…”
Section: Methodsmentioning
confidence: 99%